Factors Influencing the High Acceptance of 1 Month Injectable Birth Control at Pmb Lu'luul Maknun Surabaya - Hasanah, Lina Ishmatul; Alfitri, Rosyidah (Jurnal Midwifery, 2025)
Introduction Family planning is an effort to regulate the number of children and rugulate the desired birt spacing. So the government launched a programer method to prevent and delay pregnancy ( Sulistyawati, 2013). In the period from 2016 to 2019, the number of fertile Age Couples (PUS) in East Java Province increased, from 7,929,796 to 7,940,395. Several disticts/ cities in East Java were recorded as having fairly high number of PUS, including Malang City with 508,638. Method The method uses in this study was observasional analityic, sampling was carried out using the Accidental Sampling technique with 40 respondents. The instrumen used was a questionnaire using primary data. Result Mother age 20-35 years using 1- mont injection contraception totaled 17 people (42,5%) with (p=0,498). Mother with high school education using 1-month injection contraseption were 18 people (45,0) with (p=0,576). Working mothers who used 1-month injection contraception were 21 people (52,5%) with (p=0,704). Mothers who had UMK income were 15 people (37,5%) with (p=0,607). Primiparous mothers who used 1-month injection contraception were 10 people (25,0%) with (p=0,664). Conclusion there is no relationship between factors including age, education, occupation, income, and parity that affect the hight use of 1-mont injection contraception at PMB Lu’luul Maknun Surabaya